The Antagonists : a novel - Biswas, Tina (New Delhi : Fingerprint! Publishing, 2019)
I am one of you . . . that is why I, and only I, can be trusted to do what is good for you. January 12, 2013. Sachin Lohia, billionaire businessman, has just woken up to a nightmare. A raging fire in his hospital. Over hundred people dead. Journalists demanding answers. And worst of all, the chief minister of West Bengal, the formidable Devi, calling him a murderer. Hot-headed and stubborn, Devi doesnt bother with formalitiesor facts. Her people are baying for blood, and Sachin is the perfect scapegoat. But will her schemes bring about his downfall or will she be the one to get hurt in this battle of wits? Seamlessly melding the personal and the political, this is a darkly satirical story of clashing egos, fatal misunderstandings, and dangerous self-deception. Irreverent, incisive, occasionally scabrous, and always bold, The Antagonists shines a light on the murky world of politics.
Keywords: Indian Fiction; Crime Fiction; Political tale